DRP1 contributes to head and neck cancer progression and induces glycolysis through modulated FOXM1/MMP12 axis - Huang, Tai‐Lin; Chang, Chuang‐Rung; Chien, Chih‐Yen; Huang, Gong‐Kai; Chen, Yi‐Fan; Su, Li‐Jen; Tsai, Hsin‐Ting; Lin, Yu‐Sheng; Fang, Fu‐Min; Chen, Chang‐Han (Molecular oncology, 2022)
Abnormal DRP1 expression has been identified in a variety of human cancers. However, the prognostic potential and mechanistic role of DRP1 in head and neck cancer (HNC) are currently poorly understood. Here, we demonstrated a significant upregulation of DRP1 in HNC tissues, and that DRP1 expression correlates with poor survival of HNC patients. Diminished DRP1 expression suppressed tumor growth and metastasis in both in vitro and in vivo models. DRP1 expression was positively correlated with FOXM1 and MMP12 expression in HNC patient samples, suggesting pathological relevance in the context of HNC development. Moreover, DRP1 depletion affected aerobic glycolysis through the downregulation of glycolytic genes, and overexpression of MMP12 in DRP1‐depleted cells could help restore glucose consumption and lactate production. Using ChIP‐qPCR, we showed that DRP1 modulates FOXM1 expression, which can enhance MMP12 transcription by binding to its promoter. We also showed that miR‐575 could target 3’UTR of DRP1 mRNA and suppress DRP1 expression. Collectively, our study provides mechanistic insights into the role of DRP1 in HNC and highlights the potential of targeting the miR‐575/DRP1/FOXM1/MMP12 axis as a novel therapy for the prevention of HNC progression. This study reveals that high DRP1 expression is correlated with poor survival in patients with head and neck cancer (HNC). Moreover, DRP1 modulates growth, metastasis and glycolysis of HNC cells via a FOXM1/MMP12 axis. We note that miR‐575 targets and degrades DRP1 mRNA, inhibiting DRP1‐induced aggressive phenotypes. Our work highlights DRP1 as a potential therapeutic target for patients with HNC.